Association of GhGeBP genes with fiber quality and early maturity related traits in upland cotton - Jiayan Wu; Ruijie Liu; Yuxin Xie; Shuqi Zhao; Mengyuan Yan; Nan Sun; Yihua Zhan; Feifei Li; Shuxun Yu; Zhen Feng; Libei Li (BMC Genomics)
Abstract Transcription Factors (TFs) are key regulators of how plants grow and develop. Among the diverse TF families, the Glabrous-enhancer binding protein (GeBP) family plays a key role in trichome initiation and leaf development. The specific roles of GeBP TFs in plants remain largely unexplored, although GeBP transcription factors play important roles in plants. This study identified 16 GhGeBP genes in Gossypium hirsutum, ranging from 534 bp (GhGeBP14) to 1560 bp (GhGeBP2). Phylogenetic analysis grouped 16 GhGeBP genes clustered into three subgroups, unevenly distributed across 14 chromosomes. Analysis of the cis-acting elements revealed 408 motifs in the 2 kb upstream regions of the promoters, including stress-responsive, phytohormone-responsive, and light-responsive elements. Tissue-specific expression analysis showed 8 GhGeBP genes were highly expressed across all tissues, while GhGeBP4 and GhGeBP12 were down-regulated under conditions of drought, salt, cold, and heat stress. A genome-wide association study (GWAS) identified GhGeBP4 was associated with fiber micronaire (FM) and fiber strength (FS), while GhGeBP9 was linked to the node of the first fruiting branch (NFFB) and flowering time (FT). Haplotype analysis revealed that GhGeBP4-HAP2 exhibited higher fiber quality traits, while GhGeBP9-HAP2 was associated with early maturity. The results of this study offer significant insights that are worthy of further investigation into the role of the GhGeBP gene family in G. hirsutum and promising targets for marker-assisted selection strategies in cotton breeding programs, particularly for improving fiber quality and early maturity traits.